DYSGRAPHIA - Michael Rettig (The Advocate, 2014)
Introduction: Every teacher has probably experienced having a good student whose only problem seems to be that they take too long on writing assignments. When the student finally does turn in their work, it is sloppy, incomplete, and has several spelling errors.